THEORY AND HISTORY OF ADMINISTRATIVE SERVICES IN UKRAINE - Діденко, Сергій Володимирович; Мкртчян, Роман Сейранович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: reveals the theory and history of administrative services in Ukraine and features. Methods: historical, comparative analysis, synthesis, cognitive-analytical, etc. Results: the historical aspects and the current state of administrative services in Ukraine are elucidated. Discussion: the institute of administrative services in Ukraine needs to be improved. The historical stages of the establishment of the institution of administrative services in Ukraine can be conditionally divided into two: namely: 1) the establishment of the institute of administrative services and the adoption of the Law of Ukraine «On Administrative Services»; 2) from the moment of the adoption of the Law and to the present. Administrative service is a provision provided by the law and provided by a subject of authority of authority on the application of a natural or legal person, aimed at acquiring, changing or terminating the rights and / or duties of such person in accordance with the law and is intended to meet their needs. It is characterized by a number of features based on the principle of human-centeredness. Proceeding from a number of works devoted to the institute of administrative services, we can say that the theory of administrative services is a modern institute of administrative law, consisting of concepts and views aimed at researching, studying and developing proposals for the improvement of this institution. The theory of administrative services in Ukraine needs further elaboration and practical regulation, since the provision of services primarily depends on the effectiveness of the activity of executive authorities, civil servants and officials who are directly involved in the provision of administrative services.